A Bibliographic Sketch on Working Capital Management - Panda, Aruna Kumar (Prabandhan: Indian Journal of Management, 2010)
The present paper sincerely attempts to have a complete bibliographic sketch that is expected to acknowledge the literatures, dealing with the meaningful impact of working capital management on corporate wellbeing across the globe. In this attempt, books, edited books, research papers of referred journals having national and international importance, working papers series and doctoral dissertations of reputed world class universities, major conference proceedings, research bulletins, etc., have been collected which have either a close proximity with the management of various components of working capital or the complete theme of working capital management itself. The research materials so collected then assembled in an alphabetic order as and when they appeared, strictly as per the instructions of Harvard family of citing bibliography. It is believed that a collection of literatures of this volume and capacity would be immensely helpful to the world wide researchers to develop further insight on this aspect of financial management and, hopefully, induce them with necessary stimuli for having further empirical investigation to analyze and arrive at a suitable "liquidity-risk trade-off" point that is expected to unfold various aspects of understanding corporate liquidity and its meaningful contribution to profitability and overall working efficiency of the Organisation.